Applying the genetic algorithm and the consequential convex approximation programming for composite structure optimization - Trung, Nguyen Thoi; Phong, Ngo Thanh (Vietnam Journal of Mechanics, 2004)
This paper applies the genetic algorithm and consequential convex approximation programming to deal with problems of minimizing the strain energy of a linear elastic fiber reinforced composite laminate in a state of plane stress. The directions of fibers are used as design variables. From the numerical results, an evaluation of two optimization techniques is performed.